Regulation of the Poly(A) Status of Mitochondrial mRNA by Poly(A)-Specific Ribonuclease Is Conserved among Land Plants. (13th November 2019) - Kanazawa, Mai; Ikeda, Yoko; Nishihama, Ryuichi; Yamaoka, Shohei; Lee, Nam-Hee; Yamato, Katsuyuki T; Kohchi, Takayuki; Hirayama, Takashi
Abstract: Regulation of the stability and the quality of mitochondrial RNA is essential for the maintenance of mitochondrial and cellular functions in eukaryotes. We have previously reported that the eukaryotic poly(A)-specific ribonuclease (PARN) and the prokaryotic poly(A) polymerase encoded by AHG2 and AGS1, respectively, coordinately regulate the poly(A) status and the stability of mitochondrial mRNA in Arabidopsis. Mitochondrial function of PARN has not been reported in any other eukaryotes. To know how much this PARN-based mitochondrial mRNA regulation is conserved among plants, we studied the AHG2 and AGS1 counterparts of the liverwort, Marchantia polymorpha, a member of basal land plant lineage. We found that M. polymorpha has one ortholog each for AHG2 and AGS1, named Mp AHG2 and Mp AGS1, respectively. Their Citrine-fused proteins were detected in mitochondria of the liverwort. Molecular genetic analysis showed that Mp AHG2 is essential and functionally interacts with Mp AGS1 as observed in Arabidopsis. A recombinant MpAHG2 protein had a deadenylase activity in vitro. Overexpression of Mp AGS1 and the reduced expression of Mp AHG2 caused an accumulation of polyadenylated Mp cox1 mRNA. Furthermore, Mp AHG2 suppressed Arabidopsis ahg2-1 mutant phenotype. These results suggest that the PARN-based mitochondrial mRNA regulatory system is conserved in land plants.